Evaluating the impact of an enhanced triage process on the performance and diagnostic yield of oesophageal physiology studies post COVID-19. Issue 1 (21st December 2021) - Doyle, Rebecca; Bate, Sebastian; Devenney, Jade; Agwaonye, Sophia; Hastings, Margaret; Wych, Jane; Archbold, Sharon; Vasant, Dipesh H
Abstract : Objectives: The COVID-19 pandemic significantly impacted on the provision of oesophageal physiology investigations. During the recovery phase, triaging tools were empirically recommended by national bodies for prioritisation of referrals amidst rising waiting lists and reduced capacity. We evaluated the performance of an enhanced triage process (ETP) consisting of telephone triage combined with the hierarchical 'traffic light system' recommended in the UK for prioritising oesophageal physiology referrals. Design: In a cross-sectional study of patients referred for oesophageal physiology studies at a tertiary centre, data were compared between patients who underwent oesophageal physiology studies 6 months prior to the COVID-19 pandemic and those who were investigated within 6 months after service resumption with implementation of the ETP. Outcome measures: Adjusted time from referral to investigation; non-attendance rates; the detection of Chicago Classification (CC) oesophageal motility disorders on oesophageal manometry and severity of acid reflux on 24 hours pH/impedance monitoring. Results: Following service resumption, the ETP reduced non-attendance rates from 9.1% to 2.8% (p=0.021). Use of the 'traffic light system' identified a higher proportion of patients with CC oesophageal motility disorders in the 'amber' and 'red' triage categories, compared with the 'green' category (p=0.011). ETP also reduced the time to test for those who were subsequently found to have a major CC oesophageal motility diagnosis compared with those with minor CC disorders and normal motility (p=0.004). The ETP did not affect the yield or timing of acid reflux studies. Conclusion: ETPs can effectively prioritise patients with oesophageal motility disorders and may therefore have a role beyond the current pandemic.